Perancangan SEPIC Converter untuk Pengisian Baterai dengan Metode Kontrol PI - Rachma Prilian Eviningsih; Arief Rahmadani; Aditya Riska Kinasih (Politeknik Caltex Riau, 2023)
The electricity production generated by solar panels is not stable due to variations in the intensity of sunlight caused by fluctuating weather conditions, which results in the battery not being fully charged. To ensure a constant output voltage, a PI control method was developed in this study to regulate the duty cycle of the SEPIC converter from the solar panel. The modeling of the PI controller involved determining the P and I gains using analytical methods to obtain optimal system characteristics. The results showed that during closed-loop system testing with solar panel conditions of 1000W/m2 and a temperature of 25Â°C, the output voltage reached the set point value of 14 V with a response time of 0.6 s.